PTU-077 Unplanned hospital readmission within 30 days after liver and pancreatic resection. (28th May 2012) - Neo, E L; Viñuela, E; Bramhall, S R; Isaac, J; Marudanayagam, R; Mayer, D; Mirza, D F; Muiesan, P; Sutcliffe, R P
Abstract : Introduction: Due to limited resources within the NHS, clinicians in the UK are under constant pressure to discharge patients rapidly, even after major surgery. There is a concern that premature discharge may lead to high readmission rates and worsen clinical outcomes. The aim of this study was to evaluate the incidence and outcome of unplanned hospital readmission after liver and pancreatic resection. Methods: Patients who underwent liver or pancreatic resection between January and December 2010 were identified from a prospective database. Potential risk factors for unplanned readmission within 30 days of discharge from hospital were evaluated. Complications (Clavien grade) and 90-day mortality were also assessed. Results: The median lengths of hospital stay after liver and pancreatic resections were 6 (range 4–66) and 9 days (range 5–225), respectively. 14/174 (8%) patients were readmitted after hepatic resection. Type of liver resection was significantly associated with readmission (major 12.5% vs minor 3%; p=0.03). Of the readmitted patients, 7 (50%) had grade 3 complications, including four patients who had an uncomplicated index admission, and two patients died due to sepsis. 10/100 (10%) patients were readmitted after pancreatic resection. Readmission was more likely in patients with a pancreatic fistula (30% vs 8%, p=0.06) and a white cell count >16×10 9 /L at the time of discharge (50% vs 6%, p<0.001). Of the readmitted patients, 4 (40%) had grade 3 complications, including three patients who needed embolisation to control bleeding (two patients in this group died within 24 h). Conclusion: Hospital readmission rates after hepatic and pancreatic resection are acceptable. However, readmitted patients have a very high morbidity, often requiring urgent intervention only available at a specialist centre. Efficient communication and rapid transfer of patients to a centre with the available expertise is vital to prevent delayed deaths after major surgery. Competing interests: None declared.